2014
DOI: 10.1155/2014/671068
|View full text |Cite
|
Sign up to set email alerts
|

Fenestration Labioreduction of the Labium Minus: A New Surgical Intervention Concept

Abstract: Objectives. To test applicability of the new surgical concept for labioreduction of the labia minora. Study Design. The observational, prospective, case series study was designed. Subjects. Three consecutive subjects were included. Methods. The application of new surgical intervention was tested. Main Outcome Measures. A primary outcome measured applicability of the fenestration labioplasty and secondary measures was used to evaluate surgical resolution of medical, emotional, and social symptoms; aesthetic out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…(Z-plasty, inferior resection and superior pedicle flap reconstruction), de-epithelialized and laser labiaplasty [1][2][3][4][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Z-plasty, inferior resection and superior pedicle flap reconstruction), de-epithelialized and laser labiaplasty [1][2][3][4][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing existing techniques of labia minora reduction, like wedge resection, central V-plasty, W-plasty and central wedge nymphotomy with Z-plasty one can have a conclusion, that these methods leave transverse scars on longitudinal anatomical structure, which is labia minora [6,8,10]. Only Choi and Ostrzenski fenestration techniques treat labia minus as such, and scars are longitudinal as well and hidden [3,4]. But even these surgical techniques do not care about clitoral hood as one compartment with labia minus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Gonzalez et al [9] reported the use of the custom flask labiaplasty technique in 50 patients, which permits precise reduction of the labia minora. Ostrzenski [10] described a fenestration labiaplasty technique in which the inferior flap is transposed to reduce the height and width of the labia.…”
Section: Introductionmentioning
confidence: 99%